ANALISA JARAK TEMPUH DAN BIAYA OPERASIONAL BUS KOTA SAMARINDA - BALIKPAPAN - AFIANTARA, HAVIZ RAHMAT (KURVA S JURNAL MAHASISWA, 2018)
serving Samarinda - Balikpapan route as well as medium buses that serve Samarinda route to several sub-districts in Kutai Kartanegara upstream. According to Bappeda data and the master plan of Samarinda City Kunjang River Terminal has an area of about 906 m2 and Â± 193.876 / year number of passengers departing from this terminalIncreased ownership of four-wheeled vehicles impact on the lack of public interest in traveling by bus as mass transit, this is evident from the number of passengers who departed at the Kunjang River Terminal by bus Inter City Inside Province from Samarinda to Balikpapan and vice versaThe assessment of the performance standards of the bus assessments serving routes from the Kamarang Samarinda River Terminal to Batu Ampar Terminal based on the Department of Land Transportation (1996) and the results of the survey and analysis, were obtained;a. The service time provided by 20 bus companies commences departure from the Kunjang River Terminal at 5:51 am until 20:06 pm (05:51 - 20:06) for 14 hours 15 minutes (14:15) then this figure is in accordance with the established standard > (larger) 13 hours per day this is eligible.b. Average travel time for 3 hours 40 minutes > (greater) than the standard performance of public transport services that ranges from 60 minutes to 90 minutes because the Bus serves out-of-town transportation within the province of East Kalimantan.